2018
DOI: 10.1177/0950422218795383
|View full text |Cite
|
Sign up to set email alerts
|

Prehistoric process in HE: A critical review of institutional processes for business–academic partnerships in management development provision

Abstract: This article sets out to capture the benefits of business and universities working together to create robust management development programmes for the competitive markets ahead. It attempts to illustrate the changes in business approaches to providing people with management development, given the increased mobility of individuals from company to company, the pressures on budgets in more restricted financial times and the benefits of partnering with university provision. Using qualitative data sourced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
1
1
Order By: Relevance
“…Importantly, HEIs are often faced with the responsibility of developing new programmes as well as generating new knowledge and seeking funds to undertake research activities (Ankrah and Omar, 2015), while firms are expected to develop innovative products that appeal to the needs of customers. While this study did not reveal any relationship between the participating firms and HEIs concerning the provision of financial support for the promotion of academic programmes as well as the development of the knowledge and skills of students and staff through research activities, other authors have endorsed the importance of such collaboration (see Lee-Davies, 2019; Mensah and Enu-Kwesi, 2018; Tseng et al, 2018). When the relationship between HEIs and industry is asymmetrical – operating primarily to the benefit of only one party (in the above case, the HEI) – it does not encourage industry to continue to engage with the HEI.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Importantly, HEIs are often faced with the responsibility of developing new programmes as well as generating new knowledge and seeking funds to undertake research activities (Ankrah and Omar, 2015), while firms are expected to develop innovative products that appeal to the needs of customers. While this study did not reveal any relationship between the participating firms and HEIs concerning the provision of financial support for the promotion of academic programmes as well as the development of the knowledge and skills of students and staff through research activities, other authors have endorsed the importance of such collaboration (see Lee-Davies, 2019; Mensah and Enu-Kwesi, 2018; Tseng et al, 2018). When the relationship between HEIs and industry is asymmetrical – operating primarily to the benefit of only one party (in the above case, the HEI) – it does not encourage industry to continue to engage with the HEI.…”
Section: Discussioncontrasting
confidence: 64%
“…A study by Mensah and Enu-Kwesi (2018) found that the intention of academics to engage in research collaboration with firms was influenced by their attitude towards collaboration, their perceived control over such collaboration and their perception of the conduciveness of the environment for collaboration. Similar research by Lee-Davies (2019) revealed the importance of a strategic approach in HEIs to train senior staff to help academics understand and respond to the demands of industry–HEI collaboration and so to meet the broad objectives of their institution. In particular, we consider measures such as implementing a formal HEI–industry relationship management mechanism, implementing HEI–industry collaboration regulations, promoting a climate of innovation in the institution (Huang and Chen, 2017: 210) and obtaining input from industry into HE curricula as factors that will help to establish strong symmetrical relationships.…”
Section: Discussionmentioning
confidence: 84%